2012
DOI: 10.1108/14636641211204441
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the self‐regulation model for treatment with sexual offenders with intellectual disabilities

Abstract: PurposeThis paper aims to explore treatment implications of the self‐regulation model (SRM) for sexual offenders with an intellectual disability in an effort to provide practical applications that could be employed in treatment.Design/methodology/approachThe SRM of sexual offending proposes that difficulties in self‐regulation may lead to an increased risk of sexual offending; describing four potential pathways to sexual offending that are based on self‐regulation style and offence‐related goals. Research has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Authors have also presented a range of criminogenic treatment models developed from those established for people with IDD. These include the Good Lives Model (Ward & Brown, 2004;Ward, Mann, & Gannon, 2007;Ward, Yates, & Willis, 2012); self-regulation model (Keeling & Rose, 2012;Lindsay, Ward, Morgan, & Wilson, 2007) and various forms of psychotherapy (Cohen & Harvey, 2016). The reviews have consistently reported finding a lack of randomised control studies; a wide range of methods; a lack of consistently applied criteria for participation; an assortment of outcomes; a lack of control group or adequate control group; or a combination of these factors.…”
Section: Range Of Treatment Modalities Used With People With Idd In P...mentioning
confidence: 99%
“…Authors have also presented a range of criminogenic treatment models developed from those established for people with IDD. These include the Good Lives Model (Ward & Brown, 2004;Ward, Mann, & Gannon, 2007;Ward, Yates, & Willis, 2012); self-regulation model (Keeling & Rose, 2012;Lindsay, Ward, Morgan, & Wilson, 2007) and various forms of psychotherapy (Cohen & Harvey, 2016). The reviews have consistently reported finding a lack of randomised control studies; a wide range of methods; a lack of consistently applied criteria for participation; an assortment of outcomes; a lack of control group or adequate control group; or a combination of these factors.…”
Section: Range Of Treatment Modalities Used With People With Idd In P...mentioning
confidence: 99%